RESEARCH BARRIERS OF PUBLIC SCHOOL TEACHERS OF THE DIVISION OF ILGAN CITY - Hussien, Omar Q; Jerusalem, Rustico Y; Langam, Henry L (PUPIL: International Journal of Teaching, Education and Learning, 2019)
Teachers involved and engaged in research and utilize research evidence as the basis for instructional and pedagogical choices are leading to having desirable effects on both the teaching and learning process. The Division of Iligan City has already initiated endeavors to strengthen the research culture of the teachers. However, the number of teachers conducting teacher research is still minimal despite efforts exerted by the Division Office. Thus, this study was carried out to determine the factors and reasons why teachers are having difficulty in doing research. This study employed a descriptive research design. It used both quantitative and qualitative research methods. The study utilized a researcher-made questionnaire, and the researcher validated the questionnaire. Five (5) experts in the field of educational research were asked to validate the questionnaire. The tool’s internal reliability statistics obtained Cronbach's Alpha Coefficient of 0.942. The survey was made available in Google Forms for easy analysis and low-cost dissemination. The researchers were able to gather responses, 149 respondents. The researchers also strictly observed the ethics of research. Then the researchers analyzed the numerical data using SPSS V 20. The researchers examined the textual responses of the respondents using thematic analysis. Quantitative results revealed that teachers consider insufficiency of time to do research, no funding, too many responsibilities at school, the tedious and rigorous process in the proposal, no mentor in conducting research, and poor knowledge in analyzing qualitative and quantitative data as primary barriers to research. Teachers research activity is also hindered by no knowledge on how to make a publishable paper, very large class size in the classroom, no access to research journals, no or poor internet in the school and poor support from the management. Thematic analysis of the qualitative data also revealed the critical needs of the teachers in conducting research, which was grouped according to themes. These themes include the need for training and mentoring in research, the necessity of research funds, the need for access to research resources, the need of time, and the need for administrative support in research projects. The researchers suggested training programs using the study as the baseline data.